(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of this study was to compare different surgical methods; hemi-laminectomy versus facet protective total laminectomy in recurrence lumbar discal hernia(rLDH) patients. Materials and Methods: The patients were categorized into 2 groups:34 patients underwent total laminectomy formed the group 1, and 31 patients underwent hemi-laminectomy formed group 2. Patients were compared in terms of age, sex, body mass index(BMI), duration of surgery, length of hospital stay and complications. After 3 years, visual analogue scale for leg and back pain(VASlp,bp), oswestry disability index(ODI) scores and presence of spinal instability were evaluated. Results: There was no significiantly differences about age, sex, BMI, operation segment, mean operative time and length of hospital stay. Significant improvement was observed in both groups in terms of VAS and ODI values. Dural tear was occurred in 8 patients in group 1 and 1 patient in group 2. Superficial wound infection was seen in 1 patient in group 2. Postop spinal instability was observed in 1 patient in group 2. Conclusion: Total laminectomy increased the duration of the operation, but significantly reduced the complication rates. In recurrent disc hernias facet protective total laminectomy may be used at especially in patients without evidence of spinal instability.